Revision of mild upper eyelids dermatochalasis with plasma exeresis: A case report - Fitri, Elfa Wirdani; Sari, Ninda (Journal of Pakistan Association of Dermatologists, 2024)
Dermatochalasis is often associated with tissue aging and causes several functional and cosmetic problems. Plasma exeresis has recently been proposed as a therapy for dermatochalasis and periorbital wrinkles. This method is well tolerated, provides long-term results with a high level of satisfaction, a shorter healing period, and a very low complication rate. We present the case of a 35 years old woman with mild dermatochalasis of the upper eyelids. History of keloids, allergies of anesthesia or other drugs; as well as infection in the eyelid area are absent. Application of topical anesthesia is carried out before the procedure. Evaluation of the results of plasma exeresis measures is carried out one month after the procedure. There were significant improvements in the upper eyelids, without any scars or post inflammation hyperpigmentation. This report showed significant clinical improvement in mild dermatochalasis even only one-session of plasma exeresis. We conclude that plasma exeresis is a nonsurgical treatment option for mild dermatochalasis that is both safe and effective. If carried out appropriately, the surgery has no major side effects. Comparative study is needed to evaluate the number of plasma exeresis sessions in mild and moderate dermatochalasis.